Place of persons indicated on back photo. Accompanying texts: 'Führende Parteigenossen' and: 'Erinnerungen an Jena den 6-7. Januar 1899'
Place of persons indicated on back photo. Accompanying texts: 'Führende Parteigenossen' and: 'Erinnerungen an Jena den 6-7. Januar 1899'.